PENGARUH RANGSANGAN PERMAINAN LOGIKA SEBELUM TANDING TERHADAP PENERAPAN DAN PENGEMBANGAN TAKTIK PERMAINAN BOLA BASKET PADA TIM UKM BOLA BASKET FAKULTAS KEDOKTERAN UNPAD - Razif Fiil Ikhlas; Vita M. T. Lubis; Vitriana Vitriana (PAIFORI, 2020)
Logic is subset of philosophy that studies reasoning. This function is done by the prefrontal region. The purpose of this study is to know the effects of logical stimulation before match to the tactical application at the Basketball club in Faculty of Medicine, University of Padjadjaran. The study showed that the group that was given stimulation of logical games has a significantly higher mean (p<0.05). The conclusion of this study is logical stimulation can increase the capability of Basketball club, Faculty of Medicine, Universitas Padjadjaran.